High TXLNA Expression Predicts Favourable Outcome for Pancreatic Adenocarcinoma Patients. (25th February 2020) - Lv, Shuangyu; Zhang, Guosen; Xie, Longxiang; Yan, Zhongyi; Wang, Qiang; Li, Yongqiang; Zhang, Lu; Han, Yali; Li, Huimin; Du, Yaowu; Yang, Yanjie; Guo, Xiangqian
Abstract : TXLNA (taxilin alpha), a binding partner of the syntaxin family, was identified as a key factor in the coordination of intracellular vesicle trafficking and highly expressed in various tumor cells. However, the accurate relation between TXLNA and tumorigenesis and progression of pancreatic adenocarcinoma (PAAD) is still unclear. The present study was designed to examine the expression profile of TXLNA and explore its prognostic significance in PAAD patients and the possible molecular regulatory mechanism by analyzing a series of data from databases, including GEPIA, LOGpc, STRING, and GeneMANIA. The results indicate that TXLNA mRNA and protein were remarkably increased in PAAD tissues compared with normal pancreatic tissues. The high TXLNA expression was significantly correlated with superior overall survival (OS), disease-free interval (DFI), disease specific survival (DSS), and progression-free interval (PFI) for PAAD patients. In summary, high TXLNA expression could predict favourable OS, DFI, DSS, and PFI for PAAD patients, and it might be as potential prognostic biomarkers and targets for PAAD.